How many fish use mangroves? The 75% rule an ill‐defined and poorly validated concept. Issue 4 (28th February 2017) - Sheaves, Marcus
Abstract: Although mangroves are known to play a critical part in the lives and life histories of many fish species, these values have rarely been definitively quantified. Despite this, claims such as " an estimated 75% of commercially caught fish depend directly on mangroves " are common across a range of government and non‐government documents from around the world, to the extent that the idea that 75% or more of fish depend on mangroves has become a truism widely used to support the value of mangroves. I investigated the basis for these claims that I summarize as the "75% rule." The "75% rule" is imprecisely defined, and invariably cannot be traced back to definitive scientific data. Moreover, the claim is illogical because we simply do not have adequate knowledge of how many fish occupy different habitats or even how many species of fish there actually are. Moreover, even when the simplest proposition, of how many species use mangroves, is tested using global data bases, the best estimates fall far short of 75%. Clearly, the "75% rule" is wildly inaccurate, unsubstantiated and, at least give our current knowledge and methods, impossible to substantiate. Mangroves are critical to many species but using an indefensible pseudoscientific paradigm such as this to support conservation efforts, management actions and legal decisions, greatly weakens any arguments that build upon it, putting at risk outcomes that rely on the integrity of the claim.